Headwinds to understanding stress response physiology: A systematic review reveals mismatch between real and simulated marine heatwaves on coral reefs - Harmony A. Martell; Simon D. Donner (Climate Change Ecology)
Laboratory experiments have long been used to guide predictions of organismal stress in response to the rapidly changing climate. However, the ability to simulate real world conditions in the laboratory can be a barrier to prediction accuracy. We performed a systematic review of experimental coral bleaching literature and assembled a database to identify the methods used to measure bleaching in heating experiments and assess how closely heating experiments resembled marine heatwaves (MHWs) on coral reefs. Observations of the maximum photochemical yield of Photosystem II (FV/FM), though not a direct measure of dysbiosis, vastly outnumbered Symbiodiniaceae density and chlorophyll observations in the reviewed literature, indicating its widespread misuse as a proxy for coral dysbiosis. Laboratory studies in our database used higher maximum temperatures (∼ 0.9 ×), degree heating times (∼ 1.7 ×) and heating rates (∼ 7.3 ×), and shorter durations (∼ 1.5 ×), than MHWs on coral reefs. We then asked whether exposure differences between laboratory experiments and reef conditions altered the relationship between coral dysbiosis and heating metrics using the example of hormesis. We fit curves on the data both with and without ecologically relevant heating metrics and found hormetic curves in some response variables that were altered with the exclusion of exposures that fell outside of the bounds of MHWs on coral reefs, indicating a high likelihood of prediction error. We recommend that laboratory-based studies of coral dysbiosis use ecologically relevant exposures to improve predictions of the physiological response of corals to our rapidly warming oceans.